KEMITRAAN KONSERVASI DI TAMAN HUTAN RAYA WAN ABDUL RACHMAN, PROVINSI LAMPUNG: FAKTOR-FAKTOR PENDUKUNG DAN PENGHAMBATNYA - Mufidah, Salma; Febryano, Indra Gumay; Puspasari, Eny; Bakri, Samsul; Nurindarwati, Rini; Sugiantoro, Sugiantoro (Forestry Study Program University Of Mataram, 2024)
The conservation partnership is one of the government's efforts to harmonize the ecological, social and economic benefits of forests. This study aims to examine the factors supporting and inhibiting conservation partnerships in the Wan Abdul Rachman Forest Park. This study uses a qualitative approach. Data was collected by means of in-depth interviews and observations. The data obtained were then analyzed to determine the supporting and inhibiting factors of conservation partnerships. The results show that the supporting factors for conservation partnerships in Wan Abdul Rachman Forest Park are clear regulations, provision of productive seeds, sources of community income, diversification of non-timber forest products, improvement of community welfare, adequate capacity of human resources from managers. good. The inhibiting factors are low public understanding, lack of public trust, inadequate facilities and infrastructure, limited number of human resources from managers, lack of financial support from the government. It is necessary to carry out the intensity of socialization and assistance carried out by the manager of the Wan Abdul Rachman Grand Forest Park to the community in a sustainable manner aimed at increasing public understanding regarding conservation partnerships. Communities who have not partnered are expected to take the opportunity to enter into a cooperation agreement before there is a change in policy in the conservation area.